2014
DOI: 10.1515/jcim-2013-0053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Persea americana (avocado) fruit extract on the level of expression of adiponectin and PPAR-γ in rats subjected to experimental hyperlipidemia and obesity

Abstract: The results indicate that HAEPA exhibits hypolipidemic activity probably by increasing the mRNA expression of adiponectin and PPAR-γ, which reduce the risk of hyperlipidemia and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…Organ indices have always been regarded as important in the evaluation of immune function in animals. Research has shown that liver, kidney, and spleen indices will be lower than average when animals have an autoimmune disease, thereby indirectly reflecting the health condition of the animal . There was no significant difference ( P > 0.05) in the kidney and spleen indices amongst all treatment groups, indicating that ME LIP‐1 and NME LIP‐1 had no negative side effects on rats (Table ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Organ indices have always been regarded as important in the evaluation of immune function in animals. Research has shown that liver, kidney, and spleen indices will be lower than average when animals have an autoimmune disease, thereby indirectly reflecting the health condition of the animal . There was no significant difference ( P > 0.05) in the kidney and spleen indices amongst all treatment groups, indicating that ME LIP‐1 and NME LIP‐1 had no negative side effects on rats (Table ).…”
Section: Resultsmentioning
confidence: 96%
“…Research has shown that liver, kidney, and spleen indices will be lower than average when animals have an autoimmune disease, thereby indirectly reflecting the health condition of the animal. 17 There was no significant difference (P > 0.05) in the kidney and spleen indices amongst all treatment groups, indicating that ME LIP-1 and NME LIP-1 had no negative side effects on rats ( Table 6). In contrast, the liver index was significantly higher in the model (high-fat) group than in the other three groups (7.38 ± 0.010 versus 6.45 ± 0.007/5.77 ± 0.006/5.72 ± 0.008, P < 0.05), which may be due to the high fat content of the feed accumulating in the liver and increasing the liver index (Table 6).…”
Section: Effect Of Me Lip-1 Treatment On Organ Indicesmentioning
confidence: 88%
“…AT regulates energy homeostasis, carbohydrate as well as lipid metabolism and also IS, while AT dysfunction promotes weight gain, visceral adiposity, and IR. [25,34] Since adiponectin enhances FFA oxidation; therefore, hypoadiponectinemia would also encourage weight gain and visceral adiposity as observed in HFrC. [12] Administration of PGZ had promoted, and cinnamon extracts had reversed the weight gain in HFr fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…ADI is a ratio of visceral fat weight to body weight and expressed as adiposity percentage (%). [25] Sum of total fat pad mass -×100 Body weight ADI…”
Section: Assessment Of Weight Gain Adiposity and Adiposity Index (Adi)mentioning
confidence: 99%
“…So, identifying this potent herbs or active constituent is a good choice for study in treatment of metabolic syndrome (Sahebkar, ; Hosseinzadeh and Nassiri‐Asl, ; Razavi and Hosseinzadeh, ; Hosseini and Hosseinzadeh, ). Several plants and active constituents such as, Nigella sativa (Razavi and Hosseinzadeh, ), Rosmarinus officinalis (Hassani et al, ), rutin (a flavonoid) (Hosseinzadeh and Nassiri‐Asl, ), Allium sativum (Garlic) (Hosseini and Hosseinzadeh, ), Vitis vinifera (Grape) (Akaberi and Hosseinzadeh, ), Persea americana (avocado) (Padmanabhan and Arumugam, ), Rubus occidentalis (An et al, ), Glycyrrhizin (triterpenoid saponin of Glycyrrhiza glabra root) (Sil and Chakraborti, ), Linum usitatissimum (Flaxseed Supplementation) (Yari et al, ), Pinus pinaster (Pycnogenol® or extract from the outer bark of Pinus pinaster ) (Gulati, ), Crocus sativus (Razavi and Hosseinzadeh, ) and cinnamon obtained from genus Cinnamomum (Mollazadeh and Hosseinzadeh, ) have been used to treat metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%